Hippocampus Contributions to Food Intake Control: Mnemonic, Neuroanatomical, and Endocrine Mechanisms - Kanoski, Scott E.; Grill, Harvey J. (Biological psychiatry (1969), 2017)
Food intake is a complex behavior that can occur or cease to occur for a multitude of reasons. Decisions about where, when, what, and how much to eat are not merely reflexive responses to food-relevant stimuli or to changes in energy status. Rather, feeding behavior is modulated by various contextual factors and by previous experiences. The data reviewed here support the perspective that neurons in multiple hippocampal subregions constitute an important neural substrate linking the external context, the internal context, and mnemonic and cognitive information to control both appetitive and ingestive behavior. Feeding behavior is heavily influenced by hippocampal-dependent mnemonic functions, including episodic meal-related memories and conditional learned associations between food-related stimuli and postingestive consequences. These mnemonic processes are undoubtedly influenced by both external and internal factors relating to food availability, location, and physiological energy status. The afferent and efferent neuroanatomical connectivity of the subregions of the hippocampus is reviewed with regard to the integration of visuospatial and olfactory sensory information (the external context) with endocrine and gastrointestinal interoceptive stimuli (the internal context). Also discussed are recent findings demonstrating that peripherally derived endocrine signals act on receptors in hippocampal neurons to reduce (leptin, glucagon-like peptide-1) or increase (ghrelin) food intake and learned food reward-driven responding, thereby highlighting endocrine and neuropeptidergic signaling in hippocampal neurons as a novel substrate of importance in the higher-order regulation of feeding behavior.